National trends in age-standardized mortality attributable to hypertension in Peru - Percy Herrera-Añazco; Noé Atamari-Anahui; Maycol Suker Ccorahua-Rios; Elard Amaya (Brazilian Journal of Nephrology, 2021)
Abstract Introduction: Hypertension (HTN) is a public health problem. The prevalence and mortality rates are significantly higher in middle and low-income countries, such as Peru. This study aimed to determine the trend of mortality attributable to HTN for the 2005-2016 period in Peru. Methods: We conducted a secondary analysis based on death certificates provided by the Ministry of Health. We applied linear regression models to test the HTN mortality rate trend. Results: The age-standardized HTN mortality per 100,000 inhabitants decreased from 14.43 for the 2005 to 2010 period to 11.12 for the 2011 to 2016 period. The coast was the natural region with the highest decrease in mortality rate. Moreover, Tumbes, Callao, and Lambayeque were regions with the highest decline in mortality rate. Conclusion: The age-standardized mortality attributable to HTN decreased in Peru, with variations in both natural and political regions of the country.